2005
DOI: 10.4319/lo.2005.50.3.0799
|View full text |Cite
|
Sign up to set email alerts
|

Siliceous sponges as a silicon sink: An overlooked aspect of benthopelagic coupling in the marine silicon cycle

Abstract: Our current understanding of the silicon (Si) cycle in the ocean assumes that diatoms dominate not only the uptake of silicic acid, but also the production and recycling of biogenic silica (BSi), and that other organisms with siliceous skeletons, including sponges, radiolarians, and silicoflagellates, play a negligible role. In this study, we reexamine some aspects of the potential contribution by sponges and present in vitro evidence that BSi in the form of sponge spicules redissolves into silicic acid at far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(151 citation statements)
references
References 42 publications
8
136
1
1
Order By: Relevance
“…chuni and M. intermedia are deep-sea sponges, which live in a milieu highly under-saturated in silicon (see Maldonado et al, 2005). Therefore, it is very surprising that in this habitat these two hexactinellid sponges synthesize the largest bio-silica structures existing on earth (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…chuni and M. intermedia are deep-sea sponges, which live in a milieu highly under-saturated in silicon (see Maldonado et al, 2005). Therefore, it is very surprising that in this habitat these two hexactinellid sponges synthesize the largest bio-silica structures existing on earth (see Introduction).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested the idea that siliceous sponges are relevant DSi users at a large ecological scale, a role traditionally neglected by nutrient ecologists and biogeochemists and that is biasing the advance toward a realistic understanding of silicon cycling in marine systems, and particularly on continental margins (Reincke & Barthel, 1997;Maldonado et al, 2005Maldonado et al, , 2010aMaldonado et al, , 2011Chu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hecky et al 1973), some chrysophytes (Chrysophyceae), silicoflagellates (Dictyochales, cf. Adjou et al 2011), sponges (Porifera: Demospongiae and Hexactinellida, cf Maldonado et al 2005), or as structural support for many land plants, where BSi is precipitated in amorphous form as phytoliths (see Epstein 2001;Piperno 2006). As BSi remains are preserved relatively well in soils and sediments, and as many species produce species-specific, original structures, BSi remains are commonly used paleo-indicators in both aquatic and terrestrial environments (cf.…”
Section: Introductionmentioning
confidence: 99%